2022
DOI: 10.7441/joc.2022.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Valuing the Interest Tax Shield in the Central European Economies: Panel Data Approach

Abstract: Capital structure is one of the most frequently discussed issues within Corporate Finance Theory. Optimizing the capital structure and value of the tax shield through the evaluation of its interests can lead to the increasing value of the enterprise, followed by the rising competitiveness and flexibility. The aim of this study is to provide a novel look at the value of the interest tax shield and its determinants in the emerging economies of the Visegrad Four. The model was created on a net sample of nearly 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Further research found that the risk transfer motive of ultimate owners with high personal leverage after pledging equity, rather than the motive to avoid the transfer of control, is an influential mechanism driving the transfer of personal risk to the firm. In addition, previous literature has found that debt structure is an important factor in debt tax protection (Kovacova et al, 2022), while this paper found that debt structure also affects corporate risk-taking capacity. Moreover, previous literature has examined a firm life cycle perspective and found that firms provide distorted financial statements to obtain more favorable debt covenants (Durana et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…Further research found that the risk transfer motive of ultimate owners with high personal leverage after pledging equity, rather than the motive to avoid the transfer of control, is an influential mechanism driving the transfer of personal risk to the firm. In addition, previous literature has found that debt structure is an important factor in debt tax protection (Kovacova et al, 2022), while this paper found that debt structure also affects corporate risk-taking capacity. Moreover, previous literature has examined a firm life cycle perspective and found that firms provide distorted financial statements to obtain more favorable debt covenants (Durana et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…In line with previous research, when carrying out the principal regression hypothesis test this study controls for variables that affect corporate tax avoidance activities. Specific indicators include enterprise leverage (Lev; Kovacova et al, 2022 ), operating income growth ratio (Growth), tax collection and management intensity (TE), cash flow ratio (Cash), book-to-market ratio (BM), shareholding status of major shareholders (Top1), natural logarithm of asset size (LnSize), and Occupy and Year dummy variables for major shareholders. Table 1 gives the definitions of the variables.…”
Section: Methodsmentioning
confidence: 99%
“…According to the trade-off theory, the optimal level of leverage for a firm is the marginal benefit from an increase in debt is equal to the marginal cost of the risk of bankruptcy, and an increase in the probability of bankruptcy of a firm leads to a deviation from the optimal level of leverage in the firm's actual leverage, Howe and Jain wanted to test the accuracy of the theory by selecting US manufacturing firms in the aftermath of the terrorist attacks of 11 September 2001 and using a hypothetical test with an H 0 of a high-debt firm as opposed to a low-debt firm having a more pronounced response to the stock market reaction after the terrorist attacks is more pronounced [7].…”
Section: Case Of Us Manufacturing Companiesmentioning
confidence: 99%